ONE OF MODERN LANGUAGE TEACHING METHODS IS TASK-BASED LANGUAGE TEACHING (TBLT) DISADVANTAGES AND ITS SOLUTIONS - Bakoev , Navruzjon (Educational Research in Universal Sciences, 2024)
Task-Based Language Teaching (TBLT) is an approach to language instruction that focuses on the use of authentic language tasks as the central organizing principle for the design and delivery of language instruction. TBLT is based on the belief that language learning is most effective when it is embedded in meaningful, real-world tasks, and that learners acquire language through the process of using it to accomplish specific communicative goals